Cuticular lipids and associated gene expression analysis under NaCl stress in Thellungiella salsuginea. Issue 1 (28th January 2022) - Zhang, Pengyao; Zou, Yanli; Song, Buerbatu; Zhou, Minqi; He, Junqing; Chen, Yuan; Zhou, Yijun; Xu, Xiaojing
Abstract: Cuticular lipids, including wax and cutin, protect plants against external environmental stress. The relationship between the cuticle properties and salt tolerance is not clear. In this article, photosynthetic and physiological characteristics related to water use and cuticle permeability were assessed in the leaves of Thellungiella salsuginea under NaCl stress. The chemical composition of wax and cutin monomers, and the expression of cuticle‐associated genes were also analyzed. The results showed that the net photosynthetic rate and stomatal conductance in the leaves of T. salsuginea decreased, and the water use efficiency increased with increasing NaCl concentration. Salt stress caused a significant increase in total wax, but total cutin monomers only increased under high salt. Transcriptome sequencing and lipid metabolism pathway analysis were performed on rosette leaves of T. salsuginea after 24 h of NaCl treatment. We analyzed the expression of 42 genes involved in cuticle lipid metabolism, and found that most of them exhibited higher expression levels at 0.15 mol L −1 NaCl, but lower expression levels at 0.3 mol L −1 NaCl. The expression of 12 of these genes was further detected by qRT‐PCR after 1 week of NaCl treatment: most of them were upregulated both under low and high NaCl stress. Hence, we speculate that the cuticle acts as an adaptive trait in T . salsuginea in salty environments.